From Memorizing to Meaning-Making: Transforming Introductory Economics through Case-Based and Problem-Based Learning in Indonesian Teacher Education - Sigit Wahyudi; Silky Roudhotus Sa'adah; Salman Alfarisy Totalia (Universitas Negeri Semarang, 2026)
This study addresses persistent problems of limited conceptual understanding and low learning engagement in introductory economics by examining the implementation of an integrated Case-Based Learning and Problem-Based Learning (CBL–PBL) approach within an Economic Education program at Universitas Sebelas Maret, Indonesia. Grounded in constructivist and student-centered learning theory, the research evaluates whether this pedagogy improves students’ mastery of economic concepts, learning engagement, academic performance, and lecturers’ pedagogical effectiveness. A classroom-based design-based action research design was employed involving forty-eight first-semester students across two iterative instructional cycles using authentic economic cases, collaborative inquiry, and facilitator-guided reflection. Data were collected through validated pre- and post-tests, structured observations, and lecturer performance rubrics, and analyzed using descriptive statistics, normalized gain, and effect size measures. Findings indicate substantial improvements in conceptual mastery, rising from negligible baseline levels to more than three-quarters of students achieving proficiency, accompanied by significant growth in engagement and instructional facilitation quality. The results suggest that CBL–PBL supports deep conceptual restructuring rather than surface-level achievement. The study contributes theoretically by reinforcing constructivist problem-oriented pedagogy and practically by offering an evidence-based instructional model for higher education in Global South contexts.